2021
DOI: 10.1186/s41983-021-00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Endocan serum levels in patients with low- and high-grade meningiomas: does this biomarker have an indicative role?

Abstract: Background Meningiomas are one of the most common tumors of the brain and central nervous system. The key role of endocan in predicting tumor growth and prognosis has been shown for several types of cancers; however, this role in meningiomas has not been evaluated. In the current study, we investigated the relationship between endocan serum levels with low- and high-grade meningiomas. Results The serum level of endocan in the group with meningiomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Endocan is another potential serum biomarker of meningiomas. Endocan serum levels were found to vary in relation to meningioma grade; the higher the meningioma grade, the higher the endocan serum levels [146]. These results confirm results of a previous study that tested the levels of endocan in glioma and meningioma brain tumors and concluded that the levels of endocan are increased in tumors of glioma and meningioma patients and the amount of increase correlated with the degree of malignancy [147].…”
Section: A Serum Protein Biomarkerssupporting
confidence: 87%
“…Endocan is another potential serum biomarker of meningiomas. Endocan serum levels were found to vary in relation to meningioma grade; the higher the meningioma grade, the higher the endocan serum levels [146]. These results confirm results of a previous study that tested the levels of endocan in glioma and meningioma brain tumors and concluded that the levels of endocan are increased in tumors of glioma and meningioma patients and the amount of increase correlated with the degree of malignancy [147].…”
Section: A Serum Protein Biomarkerssupporting
confidence: 87%
“…Endocan is another potential serum biomarker of meningioma. Endocan serum levels were found to vary in relation to meningioma grade; the higher the meningioma grade, the higher the endocan serum levels [121]. These results confirm results of a previous study that tested the levels of endocan in glioma and meningioma brain tumors and concluded that the levels of endocan are increased in tumors of glioma and meningioma patients and the amount of increase correlated with the degree of malignancy [122].…”
Section: A Serum Protein Biomarkerssupporting
confidence: 87%
“…Here, we found that the levels of endocan were higher in control tumoroids in comparison with the melatonin-treated groups. One possible mechanism would be that the inner dark necrotic area contains higher levels of pro-inflammatory cytokines such as tumor necrosis factor-α and interleukin-1, leading to the induction of endocan and VEGF-A [ 37 , 38 ]. It has been indicated that the exposure of hypoxic cells to melatonin can reduce the production of angiogenesis factors [ 39 ].…”
Section: Discussionmentioning
confidence: 99%